2013
DOI: 10.1177/1071100713500656
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Nonoperative Management of Displaced Oblique Spiral Fractures of the Fifth Metatarsal Shaft

Abstract: Level II, prospective cohort study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 12 publications
(16 reference statements)
0
21
0
1
Order By: Relevance
“…A significant correlation between gender and fracture location was seen with women sustaining 75% of zone 1 2,[6][7][8] or with respect to a specific type of fracture (eg, the base of the fifth metatarsal, shaft fractures, or dancer's fractures). 3,5,[8][9][10][11][12] Fifth metatarsal fractures can be classified by location as metatarsal base fractures (zone 1, zone 2, zone 3), shaft fractures, dancer's fractures, and stress fractures. Lawrence and Botte 13 introduced the idea of the proximal fifth metatarsal fracture classification system.…”
mentioning
confidence: 99%
“…A significant correlation between gender and fracture location was seen with women sustaining 75% of zone 1 2,[6][7][8] or with respect to a specific type of fracture (eg, the base of the fifth metatarsal, shaft fractures, or dancer's fractures). 3,5,[8][9][10][11][12] Fifth metatarsal fractures can be classified by location as metatarsal base fractures (zone 1, zone 2, zone 3), shaft fractures, dancer's fractures, and stress fractures. Lawrence and Botte 13 introduced the idea of the proximal fifth metatarsal fracture classification system.…”
mentioning
confidence: 99%
“…Displaced oblique spiral fractures of the 5 th MT shaft showed excellent longterm functional outcomes when treated non-operatively with only two delayed unions and three non-union developed from 142 patients (Aynardi et al 2013).…”
Section: Non-operative Outcomementioning
confidence: 93%
“…Several studies on forefoot fractures have addressed the injuries of the some special parts such as fractures of the base of 5 th metatarsal bone (Robert Jones' fracture) or hallux and its sesamoid bones. Aynardi et al (26) nonoperatively treated 142 displaced oblique spiral fractures of the fifth metatarsal shaft. They demonstrated that nonoperative management can result in excellent and long-term functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are limited studies regarding nonoperative treatment of forefoot fractures (9,26,27), more studies are required to identify the most appropriate therapeutic modality for these patients. In the current study, we compared the clinical, radiological and subjective outcomes of treating stable metatarsal fractures with offloading shoes and short leg casting.…”
Section: Objectivesmentioning
confidence: 99%